(untitled) (Journal of Enam Medical College, 2017)
Background: Chotpoti is a popular street food among all groups of people from low to high income in most cities of Bangladesh. Objective: This study was conducted to describe the vending sites, the stalls and equipments used for food preparation, current level of food safety knowledge of vendors and the way to prepare foods to understand the risks of food contamination and opportunities for prevention. Materials and Methods: This cross-sectional study was conducted between July and October, 2012. We selected 18 popular chotpoti vending sites including market places, bus stops, road sides and amusement parks located under Dhaka city corporation areas by judgment sampling. From each study site we randomly selected six vendors for interview. A structured pretested questionnaire was used for data collection. Data were collected on (i) socio-economic and demographic characteristics of the respondents; (ii) health and personal hygiene knowledge of vendors; (iii) vendors food handling practices and (iv) source of ingredients and process of chotpoti making. Location of the chotpoti vendors, utensils used, handling of food, place of preparation of chotpoti, environment surroundings of the stall, general processing of chotpoti and hygienic practices were observed and recorded through an observation checklist. Results: We interviewed a total of 110 vendors. All vendors were male, the majority was between 21 and 30 years of age. Majority (58.2%) of the vendors acquired the knowledge of chotpoti preparation through observation. Nearly all vendors (99%) handled food with bare hands, 95% did not use aprons and hair covering and 94% handled money while serving chotpoti. Most vendors had leftovers; out of those 30% reported discarding them and the rest stored them for following days sale with inappropriate storage. Nearly one-third (32.7%) of the vendors washed their utensils with dirty water which is recycled. Majority reported that they changed the bucket water only once per 12 hours. Presence of flies was observed on food and surroundings of 33% of the stalls. Of the vendors interviewed, most of them did not have garbage receptacles and 23% disposed wastes nearby their stalls and 76% disposed in nearby dustbin. Conclusion: This study demonstrates that chotpoti vendors do not have formal education and formal training on food preparation. Moreover, lack of hand hygiene knowledge, infrequent cleaning of utensils with soap, inappropriate management of leftover foods, and lack of proper waste management create numerous possibilities for food contamination. Consumption of street vended chotpoti may pose a risk of food borne diseases and steps should be taken to educate and train the vendors on personal hygiene and food handling practices. J Enam Med Col 2017; 7(2): 69-76